BACTERIAL INFECTIONS IN PATIENTS IN ALLOGENIC STEM CELL TRANSPLANTATION PROGRAMS - Stanković, Stefan; Đunić, Irena (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Bacterial infections are common in patients enrolled in allogenic hematopoietic stem cell transplantation. Infections are the most common cause of illness and mortality in transplanted patients. The most common pathogens are Staphylococcus and Enterobacteriaceae, causing 25% of bacterial infections, each, followed by Enterococcus and P. aeruginosa.Aim: The aim of the paper is calculating the frequency of bacterial infections in patients enrolled in allogenic hematopoietic stem cell transplantation, at the Clinic for Hematology of the University Clinical Center of Serbia, as well as analyzing the epidemiological situation, the frequency of different clinical presentations of bacterial infections, and their effect on overall survival.Materials and methods: This retrospective cohort study enrolled 58 patients. The presence of bacteria was determined with standard microbial cultivation from samples. The diagnosis criteria for localized bacterial infection are a positive culture and characteristic clinical presentation. Sepsis is clinically diagnosed by a combination of a positive hemoculture and the existence of systemic inflammatory response. Management of bacterial infection starts empirically and is continued in keeping with antibiogram results. Patient survival was analyzed with the Kaplan-Meier method and compared with the log-rank test.Results: Bacterial infections were registered in 15 (25.9%) patients. The most common pathogens were Gram-negative bacteria (65.2%). The most common clinical presentation was sepsis (59.0%). Bacterial infection lethality was 60%. The Kaplan-Meier curve showed the median value for estimated patient survival in patients without bacterial infection to be 106.0 months (95% CI 85.2 – 163.3), while, for patients with bacterial infection, it was 14.0 (95% CI 8.9 – 19.1). The log-rank test showed a significant difference in the length of survival between these two groups (p < 0.001). Pseudomonas spp. was sensitive to colistin and/or meropenem. Klebsiella pneumoniae was sensitive to colistin.Conclusion: Bacterial infections are common at our clinic and are caused by endogenous opportunistic bacteria. Therefore, emphasis should be placed on the implementation of preventive measures aimed at preventing hospital-acquired infections.
Keywords: bacterial infections; allogenic hematopoietic stem cell transplantation; sepsis